(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
RAPTOR (Ricerca Archivi e Pratiche per la Tutela Operativa Regionale) is a geo-database developed in order to supply officials of the Italian Superintendences for Archaeological Heritage with a user-friendly instrument to handle those daily administrative practices that have an impact on the territory. The system, which doesn’t require any particular skill in computer sciences, allows to manage every kind of works carried out in every kind of geographical context. The mapping of the archeological outcomes is also included, so that a constant updating of the archaeological maps is possible. Part of the computer-supported procedure consists in fact of a quick recording system which allows the official archaeologist to register the basic data including the geographic features of an archaeological site or of the areas with no archaeological evidences. At the same time a more detailed analysis is also possible. Geometries can be linked to the site information sources and the whole available scientific record can be uploaded. This way, it is possible to manage also the most complex sites. This includes urban sites like Milano for which all the known archeological data are currently being recovered into the system and updated through the mapping of the archaeological dig carried out in the urban area.